Fabrication of biodegradable foams for deep tissue negative pressure treatments. Issue 5 (14th October 2017) - Warner, Harleigh J.; Wagner, William D.
ABSTRACT: Devices for negative pressure wound therapy (NPWT) rely on compressible foams operating at the tissue‐device interface. Clinically used foams are nonabsorbable and if used on deep wounds or left in place for an extended period of time, excessive cell ingrowth and formation of granulation tissue into the foam may require a surgical procedure to remove the foam. Foams with fast degradation and with low immunogenicity and fibrotic response are required. Foams composed of combinations of poly(lactide‐ co ‐glycolide) (PLGA), poly(lactide‐ co ‐caprolactone) (PLCL), and polycaprolactone (PCL) were created by combined salt leaching and solvent displacement protocols. In vitro and in vivo degradation studies and mechanical properties of foams were evaluated and compared to clinically used poly(vinyl alcohol) (PVA) foam and PCL foams. Foams composed of PLGA (50:50 lactide:glycolide) of low molecular weight blended with PCL maintained mechanical properties and degraded significantly after 21 days of subcutaneous implantation in rats. The most ideal formulations for use in NPWT were identified as copolymeric PLGA ( Mn 3000 Da) at a lactide:glycolide ratio of 50:50 combined with PCL at either a 75:25 or 50:50 ratio, and copolymeric PLGA ( Mn 7500 Da) at a lactide:glycolide ratio of 50:50 combined with PCL at a 50:50 ratio. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1998–2007, 2018.